Communication—Controlling Etching of Germanium through Surface Charge Manipulation - Wood, Joseph G.; Mitsyuk, Surge; Brayfield, Cassondra; Carpenter, Arthur; Hunt, Charles E.; van Benthem, Klaus (Journal of the Electrochemical Society, 2024)
Potassium hydroxide (KOH) aqueous solutions can effectively etch germanium. Etch rates were determined in an electrolytic etch cell. Electrically isolated Ge wafers were subject to an etch rate of 1.45 ± 0.07 nm min −1 , increasing to 12.6 ± 0.2 nm min −1 when grounded, 97 ± 2 nm min −1 when biased at −0.9 V, and 138 ± 2 nm min −1 with periodic biasing. Results suggest that the previously reported limited etching in KOH is associated with the recombination of holes with electrons injected from the surface reaction. The results of this study demonstrate that changing the hole concentration through biasing is an effective tool to control electrolytic etch rates, enabling future selective etching processes for germanium.